2015
DOI: 10.18410/jebmh/2015/1241
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Intrathecal Midazolam and Fentanyl as Additives to Intrathe Cal Hyperbaric Bupivacaine (0.5 %) for Lower Abdominal Surgeries

Abstract: BACKGROUND This prospective randomized double-blind study was designed to compare the analgesic efficacy and safety of intrathecal midazolam and fentanyl as an additive agent to bupivacaine for lower abdominal elective surgeries. METHODS Sixty patients classified in American Society of Anesthesiologists (ASA) classes I and II scheduled for lower abdominal surgeries were studied. Patients were randomly divided to receive either 12.5 mg hyperbaric bupivacaine plus 1mg midazolam (group BM, n=30) or 12.5 mg hyperb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Syed Ali Aasim et al 32 in 2015 compared the analgesic efficacy and safety of intrathecal midazolam(1mg) and fentanyl (25 µg) as an additive agent to bupivacaine for lower abdominal elective surgeries and concluded that midazolam is as effective as fentanyl in prolonging the durations of both sensory block and analgesia with less side effects like hypoxia, hypotension, bradycardia or respiratory depression. Six patients (30%) complained of pruritus in the fentanyl group while no one in other (p <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Syed Ali Aasim et al 32 in 2015 compared the analgesic efficacy and safety of intrathecal midazolam(1mg) and fentanyl (25 µg) as an additive agent to bupivacaine for lower abdominal elective surgeries and concluded that midazolam is as effective as fentanyl in prolonging the durations of both sensory block and analgesia with less side effects like hypoxia, hypotension, bradycardia or respiratory depression. Six patients (30%) complained of pruritus in the fentanyl group while no one in other (p <0.01).…”
Section: Discussionmentioning
confidence: 99%